Assessment of flow instabilities in in‐vitro stenotic arteriovenous grafts using an equivalent astable multivibrator. Issue 6 (1st September 2015) - Chen, Wei‐Ling; Lin, Yu‐Hsuan; Kan, Chung‐Dann; Yu, Fan‐Ming; Lin, Chia‐Hung
Abstract : In clinical examinations, narrowed vessel accesses will produce unsteady flow and cause changes in blood flow volume. These phenomena result in pressure, velocity and flow resistance increases and induce stress on vessel walls. The vessel wall vibrates and squeezes the low axial blood flow, a lumped resistor ( R ) representing resistance to blood flow. The compliance is a pressure against blood volume relationship, a lumped capacitor ( C ) representing the compliance capacity of the blood vessel. Vibration phenomena results on the elastic vessel wall because of transverse vibration pressure. Turbulent and instability flow will induce simple harmonic motions, and the rise time, amplitude and pulse duration of transverse vibrations are determined by the flow resistances and vessel compliances. Hence, an astable multivibrator as detection model employs time constant, τ = ( R × C ), to evaluate the flow instability and the dysfunction risk in in‐vitro arteriovenous grafts (AVGs). Experimental results show the time constants have linear regression with a positive correlation as the degree of stenosis increases. Positive pole values, s = (−1/ τ ), are used to validate that the AVG be unstable because the force responses will continuously grow with time because of vibration increases. For comparison with the computerised analysis and auscultation method, in‐vivo examinations of the proposed equivalent model can be further carried out for screening of AVG dysfunction.